Intracellular lipid transport: methods and protocols - Drin, Guillaume (Methods in molecular biology, 2019)
1. Analysis of Phosphatidylinositol Transfer at ER-PM Junctions in Receptor-stimulated Live Cells -- 2. Monitoring non-vesicular transport of phosphatidylserine and phosphatidylinositol 4-phosphate in intact cells by BRET analysis -- 3. Development of non-specific BRET-based biosensors to monitor plasma membrane inositol lipids in living cells -- 4. Following anterograde transport of phosphatidylserine in yeast in real time -- 5. Imaging lipid metabolism at the Golgi complex -- 6. Advanced in vitro assay system to measure PS and PE transport at ER/mitochondria interface -- 7. Measurement of lipid transport in mitochondria by the MTL complex -- 8. Bi- and trifunctional lipids for visualization of sphingolipid dynamics within the cell -- 9. Indirect lipid transfer protein activity measurements using quantification of glycosphingolipid production -- 10. Measurement of intracellular sterol transport in yeast -- 11. Intracellular and plasma membrane cholesterol labeling and quantification using filipin and GFP-D4 -- 12. Monitoring and modulating intracellular cholesterol trafficking using ALOD4, a cholesterol-binding protein -- 13. Measurement of Lysophospholipid Transport Across the Membrane Using Escherichia coli Spheroplasts -- 14. Preparation of proteoliposomes with purified TMEM16 protein for accurate measures of lipid scramblase activity -- 15. In vitro assays to measure the membrane tethering and lipid transport activities of the Extended Synaptotagmins -- 16. Determining the lipid binding specificity of SMP domains: an ERMES subunit as a case study -- 17. In Vitro Measurement of Sphingolipid Intermembrane Transport Illustrated by GLTP Superfamily Members -- 18. Purification and Characterization of Human Niemann-Pick C1 Protein -- 19. In vitro strategy to measure sterol/phosphatidylinositol 4-phosphate exchange between membranes -- 20. Determination of Ligand Binding Affinity and Specificity of Purified START Domains by Thermal Shift Assays Using Circular Dichoism -- 21. Synthesis of Fluorescent Membrane-spanning Lipids for Studies of Lipid Transfer and Membrane-Fusion -- 22. Setting-up all-atom molecular dynamics simulations to study the interactions of peripheral membrane proteins with model lipid bilayers. .